Enzymatic Production of Xylooligosaccharides from Xylan Solubilized from Food and Agroindustrial Waste - Pereira, Beatriz Salustiano [UNESP]; de Freitas, Caroline [UNESP]; Contiero, Jonas [UNESP]; Brienzo, Michel [UNESP] (Springer Nature, 2022)
A large volume of biomass residue is disposed daily, and the use of chemical and enzymatic treatments is an alternative to reuse it generating value-added products such as xylooligosaccharides (XOS). Banana peel, guava bagasse, orange bagasse, and restaurant pre-prepare waste were subjected to three treatments for xylan solubilization. Subsequently, xylan was enzymatically hydrolyzed to obtain xylooligosaccharides. The maximum polysaccharide solubilization using alkaline hydrogen peroxide was 90.70% from restaurant residue. Sodium hydroxide solubilized 88.01% of xylan from guava bagasse and 74.20% of xylan from the banana peel, using potassium hydroxide. After enzymatic hydrolysis, the maximum production of XOS was 54.14% with banana peel residue (peroxide solubilized), 59.86% with guava bagasse (sodium hydroxide solubilized), 50.42% for orange bagasse (peroxide solubilized), and 50.80% with restaurant residue (potassium hydroxide solubilized). The results showed that each of the biomass had a different condition of treatment. The best conditions to obtain xylan from banana peel and guava bagasse were using NaOH treatment, and from orange bagasse and restaurant pre-prepare were using KOH. To produce XOS, banana peel and orange bagasse were treated with peroxide, and the guava bagasse and restaurant residue were treated with potassium hydroxide and subsequently submitted to enzymatic hydrolysis for 12 and 48 h.
Keywords: Alkaline hydrogen peroxide; Aspergillus versicolor; Bioactive compounds; Biomass; Endoxylanase; Hemicellulose